2018
DOI: 10.1590/s0102-865020180090000010
|View full text |Cite
|
Sign up to set email alerts
|

Potencial of different hydroxyapatites as biomaterials in the bone remodeling

Abstract: To analyze the therapeutic potentials of different hydroxyapatites used for the correction of bone defects in rats. Methods: Forty rats, male, albino wistar, were distributed in 4 groups. They were submitted to a 3.5 mm defect in tibia. They received low purity hydroxyapatite, Strontium hydroxyapatite and hydroxyapatite doped with gallium, having a seven day evaluation time. Histopathology slides were stained with hematoxylin-eosin, for morphological evaluation. Were analyzed inflammatory processes, necrosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Gallium ions are significantly less toxic than silver and have a different antibacterial mechanism, primarily based on the substitution of iron ions in protein metabolism, which leads to the disability of cell functions. Notably, gallium ions show positive effects on bone tissue through the induction of osteoblasts and protection from increased resorption by inhibiting osteoclast activity and modifying crystal solubility, which is harnessed in the treatment of osteoporosis [ 24 , 26 , 27 , 28 , 29 ]. Therefore, simultaneously enriching HA with silver and gallium ions may lead to a material characterized by high antibacterial efficiency and low toxicity to human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Gallium ions are significantly less toxic than silver and have a different antibacterial mechanism, primarily based on the substitution of iron ions in protein metabolism, which leads to the disability of cell functions. Notably, gallium ions show positive effects on bone tissue through the induction of osteoblasts and protection from increased resorption by inhibiting osteoclast activity and modifying crystal solubility, which is harnessed in the treatment of osteoporosis [ 24 , 26 , 27 , 28 , 29 ]. Therefore, simultaneously enriching HA with silver and gallium ions may lead to a material characterized by high antibacterial efficiency and low toxicity to human cells.…”
Section: Introductionmentioning
confidence: 99%
“…The doping with gallium was effective in inducing an antibacterial effect against bacterial and fungus strains, without reducing the viability of human cells. Cassino et al [ 129 ] studied gallium doped HA in in-vivo bone remodeling with Wistar rats, observing an improvement in the repair of the bone defects. The in-vivo study showed that gallium doped HA is an effective osteoinductive and osteoconductive agent, making it a promising candidate for bone regeneration applications.…”
Section: Gallium In Calcium Phosphate Bioceramicsmentioning
confidence: 99%
“… Improved the repair of bone defects. [ 129 ] Precipitation method and solid-state reaction Hydroxyapatite (Ga content up to 0.35 mass%) Characterization of ceramic by TEM, ICP-OES, XRD, FTIR, and NMR. Cell viability assay using BALB/c 3T3 cells.…”
Section: Gallium In Calcium Phosphate Bioceramicsmentioning
confidence: 99%
“…It should be noted that Ga ions exhibit antiresorptive and antiosteoporotic properties, as well as antitumor, anti-inflammatory and immune suppressive properties [26,35,36]. As a result, HA doped with gallium can be used as biomaterial, which on the one hand enhances bone growth and on the other hand protects from bacterial infection [37][38][39][40]. In the available literature, the use of the aforementioned biomaterial as a drug delivery system is reported [41][42][43].…”
Section: Introductionmentioning
confidence: 99%